2021
DOI: 10.3390/foods11010100
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Traditional Varieties of Apricots (Prunus armeniaca L.) of the Campania Region, Southern Italy

Abstract: Campania is the most important region of Italy in the apricot cultivation, present mostly in the Vesuvio area. At least to the best of our knowledge, no studies are reporting the biochemical characterization of the considerable number of traditional apricot varieties present on this territory, including the qualitative and quantitative profile of the polyphenols present. Our work evaluated the content of β-carotene, total phenolics, phenolic profiles, ascorbic acid and antioxidant activity of 23 traditional va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 54 publications
7
11
0
Order By: Relevance
“…The varieties "Boccuccia liscia" and "Baracca" exhibited TP contents equal to 19.16-mg 100-g −1 FW and 30.22-mg 100-g −1 FW, respectively. These values were slightly lower than or similar to those observed by Fratianni et al (28). Once again, the varieties of apricot cultivated in the Campania region, particularly in the Vesuvius territory, showed a higher TP content relative to that shown by the Iranian variety "Nouri, " analyzed by Nourozi et al (56), and to that found by Kasapoglu et al in some Turkish apricot varieties (57); however, it was similar to that of other varieties cultivated in the Mediterranean area, such as "Nereis" (58).…”
Section: Total Polyphenol Contentsupporting
confidence: 76%
See 4 more Smart Citations
“…The varieties "Boccuccia liscia" and "Baracca" exhibited TP contents equal to 19.16-mg 100-g −1 FW and 30.22-mg 100-g −1 FW, respectively. These values were slightly lower than or similar to those observed by Fratianni et al (28). Once again, the varieties of apricot cultivated in the Campania region, particularly in the Vesuvius territory, showed a higher TP content relative to that shown by the Iranian variety "Nouri, " analyzed by Nourozi et al (56), and to that found by Kasapoglu et al in some Turkish apricot varieties (57); however, it was similar to that of other varieties cultivated in the Mediterranean area, such as "Nereis" (58).…”
Section: Total Polyphenol Contentsupporting
confidence: 76%
“…On the other hand, other varieties exhibited a level of TPs similar or more than three times higher relative to "Vitillo, " with values ranging from 28.67-mg 100-g −1 FW ("Puscia") to 30.22-mg 100-g −1 FW ("Baracca") and 31.32-mg 100-g −1 FW ("Preveta bella") to 34.04-mg 100-g −1 FW ("Vollese"). This last variety exhibited a TP content very similar to that found in the variety "Boccucia Eboli" (28). In any case, except for the variety "Vitillo, " none of the varieties we analyzed showed a total polyphenol content lower than 12-mg 100-g −1 FW −1 .…”
Section: Total Polyphenol Contentsupporting
confidence: 69%
See 3 more Smart Citations